Risk of invasive prostate cancer and prostate cancer death in relatives of patients with prostatic borderline or in situ neoplasia: a nationwide cohort study - Xu, Xing; Fallah, Mahdi; Tian, Yu; Mukama, Trasias; Sundquist, Kristina; Sundquist, Jan; Brenner, Hermann; Kharazmi, Elham (Cancer, 2020)
The question of whether having a family history of prostatic borderline or in situ neoplasia (PBISN) is associated with an increased risk of invasive prostate cancer (PCa) or death from PCa remains unanswered. The objective of the current study was to provide an evidence-based risk estimation for the relatives of patients with PBISN.